3-D-Glucopyranosyl-6-methoxy-2-benzoxazolinone (MBOA-N-Glc) is an insect detoxification product of maize 1,4-benzoxazin-3-ones - Maag, Daniel; Dalvit, Claudio; Thevenet, Damien; Köhler, Angela; Wouters, Felipe C.; Vassão, Daniel G.; Gershenzon, Jonathan; Wolfender, Jean-Luc; Turlings, Ted; Erb, Matthias; Glauser, Gaetan (My University, 2014)
In order to defend themselves against arthropod herbivores, maize plants produce 1,4-benzoxazin-3-ones (BXs), which are stored as weakly active glucosides in the vacuole. Upon tissue disruption, BXs come into contact with ?-glucosidases, resulting in the release of active aglycones and their breakdown products. While some aglycones can be reglucosylated by specialist herbivores, little is known about how they detoxify BX breakdown products. Here we report on the structure of an N-glucoside, 3-?-d-glucopyranosyl-6-methoxy-2-benzoxazolinone (MBOA-N-Glc), purified from Spodoptera frugiperda faeces. In vitro assays showed that MBOA-N-Glc is formed enzymatically in the insect gut using the BX breakdown product 6-methoxy-2-benzoxazolinone (MBOA) as precursor. While Spodoptera littoralis and S. frugiperda caterpillars readily glucosylated MBOA, larvae of the European corn borer Ostrinia nubilalis were hardly able to process the molecule. Accordingly, Spodoptera caterpillar growth was unaffected by the presence of MBOA, while O. nubilalis growth was reduced. We conclude that glucosylation of MBOA is an important detoxification mechanism that helps insects tolerate maize BXs.
Keywords: Zea mays; Poaceae; Spodoptera; Ostrinia nubilalis; Plant defence; Secondary metabolites; 1; 4-Benzoxazin-3-ones; MBOA; MBOA-N-Glc; Detoxification